Przetwarzanie danych osobowych przez gminne ośrodki pomocy społecznej w ramach przyznawania świadczeń z pomocy społecznej - Węgrzyn, Justyna (Wydawnictwo Uniwersytetu Wrocławskiego, 2021)
The purpose of this study is to analyze art. 100 of the Act on Social Assistance as amended by the Act implementing the GDPR. The scope of these considerations includes: identification of the data controller; indication of the categories of data processed; implementation of the information obligation resulting from Article 13 and Article 14 GDPR; measures securing the processing of personal data and the duty of confidentiality.
Keywords: Regulation 2016/679 (GDPR); Act on Social Assistance; personal data; processing personal data; communal social welfare center